Pelatihan Pembuatan Aplikasi Forecasting bagi Anggota Kelompok Kajian Pasar Modal Universitas Muria Kudus - Tutik Khotimah; Evanita Evanita (Universitas Muria Kudus, 2019)
The Capital Market Study Group (KKPM) is one of the Student Activity Units in the Faculty of Economics and Business, Muria Kudus University. Its members consist of Management students and Accounting students who are interested in capital markets. Forecasting capabilities are needed for people who want to invest in the world of capital markets. This ability can be used for better decision making in investing. However, the knowledge and abilities of KKPM members on forecasting are still lacking. Therefore, forecasting training has been held. There were 21 people who attended the training. The first activity was given material about forecasting with Linear Regression. The second activity was carried out training and assistance in making forecasting applications with PHP and MySQL programming languages. In addition to aiming to improve student forecasting skills, this training can increase the ability of students to make forecasting applications.